An investigation of tourists satisfaction in Malaysia cultural museum: entrance space experience - Ab Rahman, Syakir Amir; Zakir, Muhammad Irham; Abdullah, Alias; Abdul Razak, Rajabi; Abdul Majid, Noor Hanita; Harun, Nor Zalina; Abu Bakar, Aisyah (Quantum Academic Publisher Enterprise, 2024)
Malaysia is known with its rich and diverse cultural heritage. Therefore, a number of cultural museums which display Malaysia’s multifarious history, traditions, and art forms has established. However, there is a decreasing trend of visitor visiting the cultural museum in Malaysia. This trend is highly influenced by the tourists’ experience gained during their visit to the museum. This study aims to study the tourist satisfaction in the entrance space of Malaysia cultural museum. This study analyses the data gathered from 381 respondents through a questionnaire survey. The statement in the survey represents different elements which are education, escape, aesthetic, and entertainment. The findings show that the aesthetic element is the most appreciated element by the respondents during the visit while escape element is the least appreciated element. Most of the respondents are in the younger group age, which is an age group that appreciates aesthetics the most while almost a third of the respondents went to the museum due to work, hence make the element of escape the least appreciated. From history, museum institutions have been evolving throughout the time as it is only known as a place called “Cabinets of Curiosities” in 1500s. The existing museum can start integrating itself with other attractions or providing more activities for the visitor to turn it into a more interesting and fun place for the visitor.